DeyPoS: Deduplicatable Dynamic Proof of Storage for Multi-User Environments (International Journal of Engineering and Computer Science, 2017)
Dynamic Proof of Storage (PoS) is a useful cryptographic primitive that allows a user tocheck the integrity and efficiently update the files in a cloud server. There has been many solutions proposedfor Dynamic Proof of Storage in singleuser environment but for multi user problems is still unsolvable. Amulti-user cloud storage system needs the secure client side cross user deduplication technique, whichallows a user to stop the uploading process and gain the ownership of the files immediately, when otherowners of the same files have uploaded them to the cloud server.As we know, none of the existing dynamicPoSs can support this technique. In this paper, we elaborate the concept of deduplicatable dynamic proof ofstorage and propose an efficient construction called DeyPoS, to achieve dynamic Proof of Storage andsecure cross-user deduplication, simultaneously.To build a novel tool called Homomorphic AuthenticatedTree (HAT) to address challenges such as structure diversity and private tag generation.Hence we prove thesecurity of our construction, and the theoretical analysis and experimental results show that our research ispractically valid and applicable.